Scattering of a spinning dielectric sphere to polarized plane waves; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 329 - Tang Huan; Shi Zhuoyuan; Zhang Yuan; Li Renxian; Wei Bing; Gong Shuhong; Minin I. V. Igor Vladilenovich; Minin O. V. Oleg Vladilenovich (2024, 2024)
Title screen